PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA APARATUR DI LINGKUP KECAMATAN PAMEKASAN KABUPATEN PAMEKASAN - jurnalmap map; Fausi Santoso; Indra Prasetyo; Chamariyah ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
ABSTRACT This research was conducted in Pamekasan District Scope of Pamekasan Regency. with a total sample of 36 people. The purpose of this study is 1) To know the motivation, work environment and organizational culture simultaneously have an influence on the performance employee, 2) To know the motivation, work environment and organizational culture partially have influence on apparatus performance of employee, 3) To know among the motivation, work environment and organizational culture that has a dominant influence on the performance of employee. The results showed that simultaneously, motivation, work environment and organizational culture have a very significant effect on employee performance. Partially, motivation, work environment and organizational culture have a significant influence on the performance of employee. Motivation variables have a very dominant influence in mempengruhi apparatus performance in the scope of Pamekasan District Pamekasan. Keywords: Motivation, Work Environment, Organizational Culture and Employee Performance.